Exploring electric vehicle consumer behavior: impact of digital innovation, environmental concern, perceived value, and social influence on purchase intentions - Kottala, Sri Yogi; Chanagala, Shankar; Balaji, Chintala; Reddy, V. V. Narsi; Babu, G. N. P. V. (Frontiers in Sustainable Cities, 2025)
BackgroundUnderstanding the drivers and boundary conditions of electric vehicle (EV) adoption is critical to fostering sustainable transportation. Building on perceived value and planned behavior theories, this study proposes a moderated mediation model in which perceived value influences both sustainability perception and purchase intentions, with household income, technology trust, and environmental knowledge serving as moderators.MethodsA cross-sectional survey of 496 licensed drivers familiar with EVs was conducted using validated multi-item scales. Data were analyzed in R using confirmatory factor analysis and structural equation modeling (lavaan), incorporating product-indicator interactions and 5,000-sample bootstrapping to test the direct, moderating, and mediating effects.ResultsConsumers’ perceived value has a positive effect on sustainability perception (0.122, p < 0.001) and purchase intentions (0.002, p < 0.001). Household income also strengthens the relationship between perceived value and purchase intention (0.043, p < 0.001). Digital innovation (0.285, p < 0.001) and environmental concerns (0.411, p < 0.001) dynamically influenced the perception of sustainability at a significant level, although social influence was not significant. Compared with other variables, sustainability perception had the greatest effect on consumers’ intention to buy an electric car (0.624, p < 0.001) and served as a mediator in three out of four indirect connections between perceived value and purchase intention. The moderating effects of technology trust and environmental knowledge were not supported.ConclusionThese findings highlight the central roles of value and sustainability perceptions in EV adoption and identify income as a key boundary condition. Practical implications include tailoring incentives by income segment, investing in user-centric digital platforms, and emphasizing both economic and environmental benefits. Theoretically, this study extends technology acceptance models by integrating sustainability constructs and underscores the nuanced impact of socioeconomic factors on green consumer behavior.